Транспортна задача з нечітко заданими потребами в матеріальних ресурсах - Ощепков, Є. С. (ХНУРЕ, 2024)
The paper explores the application of fuzzy logic to the transportation problem where demands for material resources are imprecisely defined. Fuzzy logic, with its concept of fuzzy sets and rules, is employed to handle uncertainty in input data, crucial for logistics systems. This study modifies the standard transportation task by incorporating fuzzy demands, reflecting the uncertainty or fluctuations in demand. The objective is to develop a supply plan that minimizes total costs while satisfying consumers’ fuzzy demands to the maximum extent possible, thereby maximizing overall confidence in the plan’s cost-effectiveness and consumer satisfaction.
Keywords: транспортна задача; нечітка логіка